Non pharmacological Methods to Reduce Pain in The First Stage of Labor with a Counter Pressure Technique - Domas Nurchandra Pramudianti (UrbanGreen, 2020)
The Pain is a natural process of labor, but if not handled properly, it will cause another problem, namely increasing anxiety in the labour process. Nowadays many methods are offered to reduce pain in labor, both pharmacological (using drugs) and non pharmacological methods. If possible the choice of non-pharmacologic therapy for the management of pain in pregnancy and labor should be considered before using analgesic drugs. One of an effective non-pharmacological method to reduce pain is with massage Counter Pressure. Article searching conducted in some databases: Google Scholar, Proquest and Science Direct. Keyword used were “Counter Pressure”, “pain”, Labour”and finally got 9 articles matched. Counter Pressure could be categorized as a safe and effective intervention to reduce labor pain at first phase